The relationship between job satisfactions and turnover intentions among associates in Putrajaya Marriott Hotel / Nurul Syafawani Mohd Poad - Mohd Poad, Nurul Syafawani (Faculty of Business and Management, 2017)
This quantitative research aims to examine the impact of job satisfaction through work value, compensation and benefits, and working environment that influence turnover intention among associates in Putrajaya Marriott Hotel. This includes the objectives as follows, to investigate the relationship between work value and turnover intentions among associate in Putrajaya Marriott Hotel, to examine the relationship between compensation and benefits and turnover intentions among associate in Putrajaya Marriott Hotel, to study the relationship between work environment and turnover intentions among associate in Putrajaya Marriott Hotel, and to identify the most significant factors that influence turnover intentions among associate in Putrajaya Marriott Hotel. Most of the intention of associates’ to have turnover intentions are influence by surrounding factors such their compensation and benefits. This factor are the main factor that always seen roughly by the organization. But there are other factors that influence to turnover intentions such work value and work environment. The data has been collected from in Putrajaya Marriott Hotel which include executive and non-executive associates by distributing questionnaire to the 200 associates that been simple random sampling. The results showed that all independent variables for this study which are work value, compensation and benefits, and working environment are significant with turnover intentions. This study is said to be beneficial to the organization in order to reduce the number of associates’ turnover intention. Recommendation for future is also have been discussed.